Cross-Sectional Associations between Dietary Daily Nicotinamide Intake and Patient-Reported Outcomes in Colorectal Cancer Survivors, 2 to 10 Years Post-Diagnosis - Wenbo Wu (MDPI AG, 2021)
Supplementation with nicotinamide adenine dinucleotide (NAD+) precursors including dietary nicotinamide has been found to boost tissue NAD+ levels and ameliorate oxidative stress-induced damage that contributes to aging and aging-related diseases. The association between dietary NAD+ precursors and patient-reported health-related outcomes in cancer survivors has not been investigated. This study aimed to determine associations of dietary nicotinamide intake with different patient-reported outcomes in colorectal cancer survivors, 2 to 10 years post-diagnosis. A total of 145 eligible participants were recruited into this cross-sectional study. Dietary nicotinamide intake level was calculated based on data from 7-day food diaries. Fatigue was assessed with the Checklist Individual Strength (CIS), which is a subscale of the cancer-specific European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC), and anxiety and depression were assessed with Hospital Anxiety and Depression Scale (HADS). Oxidative stress marker serum protein carbonyl contents and serum NAD+ levels were measured. A hierarchical linear regression model with confounder adjustment was performed to analyze the association of nicotinamide intake, serum protein carbonyl contents, and NAD+ levels with patient-reported outcomes. The median values of daily nicotinamide intake for male and female participants were 19.1 and 14.4 mg, respectively. Daily dietary nicotinamide intake was associated with a lower level of fatigue (β: −14.85 (−28.14, −1.56)) and a lower level of anxiety and depression (β: −4.69 (−8.55, −0.83)). Subgroup analyses by sex showed that a beneficial association between nicotinamide intake and patient-reported outcomes was mainly found in men. To conclude, our findings suggested that higher dietary NAD+ precursor nicotinamide intake was cross-sectionally associated with less patient-reported outcomes in CRC survivors.